2017
DOI: 10.1007/s13204-017-0581-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective Pb2+ removal from water using nanozerovalent iron stored 10 months

Abstract: Heavy metal removal from water required reliable and cost-effective considerations, fast separation as well as easy methodology. In this piece of research, nanozerovalent iron (NZVI) was prepared as ideal sorbent for Pb 2? removal. The sample was characterized using X-ray diffraction (XRD), high-resolution transmission electron microscope (HRTEM), and atomic force microscope (AFM-SPM). Batch experiments comprised the effect of pH value and contact time on the adsorption process. The same NZVI was stored for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The resulting spectra are showed in Figure 2 the use of ethanol, iso-propanol is also described as a protective layer for nZVI particles [25]. The stability of stored particles is recently studied by Ahmed and authors who showed that extended storage with no corrosion on nZVI particles was achieved using polyvinyl pyrrolidone [4]. We observed the same and unchanged XRD pattern of ethanolic suspension after one month from preparation.…”
Section: Characterization Of Pdca-nzvi Particles From One-pot Synthesissupporting
confidence: 64%
See 2 more Smart Citations
“…The resulting spectra are showed in Figure 2 the use of ethanol, iso-propanol is also described as a protective layer for nZVI particles [25]. The stability of stored particles is recently studied by Ahmed and authors who showed that extended storage with no corrosion on nZVI particles was achieved using polyvinyl pyrrolidone [4]. We observed the same and unchanged XRD pattern of ethanolic suspension after one month from preparation.…”
Section: Characterization Of Pdca-nzvi Particles From One-pot Synthesissupporting
confidence: 64%
“…Zeta-potential of incubated PDCA-nZVI showed negative values. By comparing the obtained results with the study on Pb removal using nZVI particles [4], where the changes in surface charge was examined, we could find some common ground. This is because of very [25].…”
Section: Characterization Of Pdca-nzvi Particles From One-pot Synthesismentioning
confidence: 82%
See 1 more Smart Citation
“…Lead metal ion removal experiment from wastewater has indicated that the pH of the solution where lead ion is found affects the state or species of nZVI adsorbent used for adsorption; at lower pH, the surface oxide layer is positively charged where it is dominated by protonated ions and attract only the positive ions, whereas at higher pH its surface becomes negatively charged and forms surface complexes with heavy metals such as Cd, Cu, Pb and others. 50 In the report, it was justified that increasing contact time, pH and nZVI dose increases the removal of the contaminant. However, adsorbate concertation has an inverse relation with the removal capacity.…”
Section: Heavy Metal (Pb CD and Cu) Removal Efficiency Of Nzvimentioning
confidence: 99%
“…However, adsorbate concertation has an inverse relation with the removal capacity. Ahmed et al (2017) 50 have reported about 98% of lead removal from water after 10 hours of contact time. The authors reported that the physical properties, magnetic susceptibility, and conductance of nZVI were correlated with adsorption efficiency.…”
Section: Heavy Metal (Pb CD and Cu) Removal Efficiency Of Nzvimentioning
confidence: 99%